Aryl Hydrocarbon Receptor Promotes IL-10 Expression in Inflammatory Macrophages Through Src-STAT3 Signaling Pathway - Zhu, Junyu; Luo, Li; Tian, Lixing; Yin, Shangqi; Ma, Xiaoyuan; Cheng, Shaowen; Tang, Wanqi; Yu, Jing; Ma, Wei; Zhou, Xiaoying; Fan, Xia; Yang, Xue; et al. (Frontiers in Immunology, 2018)
The aryl hydrocarbon receptor (AhR) is an important immune regulator with a role in inflammatory response. However, the role of AhR in IL-10 production by inflammatory macrophages is currently unknown. In this study, we investigated LPS-induced IL-10 expression in macrophages from AhR-KO mice and AhR-overexpressing RAW264.7 cells. AhR was highly expressed after LPS stimulation through NF-κB pathway. Loss of AhR resulted in reduced IL-10 expression in LPS-induced macrophages. Moreover, the IL-10 expression was elevated in LPS-induced AhR-overexpressing RAW264.7 cells. Maximal IL-10 expression was dependent on an AhR non-genomic pathway closely related to Src and STAT3. Furthermore, AhR-associated Src activity was responsible for tyrosine phosphorylation of STAT3 and IL-10 expression by inflammatory macrophages. Adoptive transfer of AhR-expressing macrophages protected mice against LPS-induced peritonitis associated with high IL-10 production. In conclusion, we identified the AhR-Src-STAT3-IL-10 signaling pathway as a critical pathway in the immune regulation of inflammatory macrophages, It suggests that AhR may be a potential therapeutic target in immune response.